ELECTROMAGNETIC WAVE EQUATION ON DIFFERENTIAL FORM REPRESENTATION - Handayana, I Gusti Ngurah Yudi (Indonesian Physical Review, 2018)
One of the indispensable part of the theoretical physics interest is geometry differential. This one interest of physical area has been developed such as in electromagnetism. Maxwell's equations have been generalized in two covariant forms in differential form representation. A beautiful calculus vector in this representation, such as exterior derivative and Hodge star operator, lead this study. Electromagnetic wave equation has been expressed in differential form representation using Laplace-de Rham operator. Explicitly, wave equation shows the same form in Minkowski space-time like vector representation. This study is able to introduce us to learn application of Â differential form in physics.